Analysis Of Textbook â€œAku Cinta Bahasa Arabâ€ : Cognitive of Taxonomyâ€™s Bloom/ ØªØÙ„ÙŠÙ„ Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ù…Ø¯Ø±Ø³ÙŠ "Aku Cinta Bahasa Arab" Ø§Ù„Ø¥Ø¯Ø±Ø§Ùƒ Ù…Ù† Ø¨Ù„ÙˆÙ… Ø§Ù„ØªØµÙ†ÙŠÙ - Barkah Nur Fauziah, Siti Anne; Zaid, Abdul Hafidz; Zarkasyi, Ahmad Hidayatullah; Mahmudi, Ihwan; Yasin, Agus (Ijaz Arabi Journal of Arabic Learning, 2021)
This study aims to determine the quality of textbook content Aku Cinta Bahasa Arab in terms of the cognitive aspects of Bloom's taxonomy. This research is a qualitative descriptive study. The main data sources are the textbooks of Aku Cinta Bahasa Arab. The analysis was done by analyzing the teaching materials using cognitive qualifications on Bloom's taxonomy. The analysis results show that Aku Cinta Bahasa Arab book achieves excellent results on qualification C1, C2, C3 the result of analysis is good at C4, C5, and C6. The material presented represents operational verbs in meeting low-level learning needs very well, but only enough to represent operational verbs in meeting high learning needs.